Integrated flue gas CO2 capture and conversion to formate: a sustainable approach - Kumar, Rohit; Majumder, Supriyo; Singh, Chadrodai Pratap; Samanta, Chanchal; Newalkar, Bharat L.; Krishnamurty, Sailaja; Das, Raj Kumar (ChemSusChem, 2025)
Industrial CO2 emissions, characterized by dilute streams and impurity complexity, demand energy-efficient mitigation strategies beyond conventional capture technologies. Here, an integrated CO2 capture and conversion (ICCC) system is reported employing a heterogenized iridium catalyst-hydroxyquinoline-ligated Cp*Ir-Cl immobilized on amine-functionalized silica-that directly converts CO2 from synthetic flue gas containing SOx, NOx, and O2 to formate with 100% selectivity. The catalyst delivers remarkable activity, achieving turnover numbers up to 10,286 within 16 h. Density functional theory reveals that its square pyramidal geometry, induced by the hydroxyquinoline ligand, enhances Ir-N(ring) bond strength and electronic delocalization, thereby improving hydration energy, structural robustness, and catalytic efficiency. Importantly, the catalyst system demonstrates excellent durability, maintaining full activity over five regeneration cycles. Hydrogenation in a 1 M DABCO medium, followed by thermal decomposition of the amine-formate adduct at 150 degrees C, enables efficient lean amine regeneration, allowing subsequent flue gas capture and formate production without performance loss. This closed-loop strategy delivers a sustainable, contaminant-tolerant, and recyclable CO2-to-formate platform with strong promise for scalable industrial deployment.
Keywords: CO2 capture; flue gases; integrated capture and conversions; net zero future; Recycle